What do we know about consumers’ attitudes towards cultured meat? A scoping review - C.Z. Tsvakirai; L.L. Nalley; M. Tshehla (Future Foods, 2024)
Scientific breakthroughs in lowering cultured meat's production cost have ignited the hope of developing a global cultured meat industry. This has resulted in a surge in consumer psychology studies on cultured meat, as researchers have sought to determine the antecedents of cultured meat's acceptance and consequently acquire insights into the demand feasibility of the envisaged industry. However, the literature is fragmented; hence, this study aims to summarize the state of knowledge and consolidate the findings of this literature. A secondary purpose was to reflect on the depth of evidence, highlight the major findings and identify gaps/trends in knowledge. The study noted growing trends in conducting research that takes a holistic view of consumer psychology around cultured meat. Nuances were identified in studies that involved actual tasting of cultured meat, carrying out comparative studies, using novel data sets and studies focused on demographic segments of interest. The evidence-based knowledge reported in this paper is useful to support the further development of the cultured meat industry and helps to highlight these areas of growth in the literature.